Using social media platforms to prepare for examinations post Covid-19: The case of saudi university EFL learners - Abdullah Al Fraidan; Ebtisam Mohammed Al-Harazi (Heliyon, 2023)
Mobile-Assisted Language Learning (MALL) applications have been increasingly used by learners and instructors after the government imposed social and educational restrictions in Saudi Arabia for almost two years due to the Covid-19 pandemic. This research investigates Saudi EFL university learners’ use of MALL applications, specifically Social Media Platform (SMP) applications, in their preparation for achievement exams post the Covid-19 pandemic social and educational restrictions. A questionnaire consisting of questions, as well as a range of open-ended question was designed and administered to 125 English major female learners who were enrolled at King Faisal University (KFU) in two different educational modes viz., regular (66) and distance (59) participation. Seven SMP applications – WhatsApp, YouTube, Telegram, Twitter, Instagram, Snapchat and Facebook – were used in this study. Data were analyzed quantitatively using the MANOVA test in SPSS, and qualitatively. The results have shown that both Regular Learners (RLs) and Distance Learners (DLs) used SMPs to prepare for their exams. The data analysis revealed that there were significant differences between RLs and DLs in their frequency of use of SMPs in preparation for exams. WhatsApp was the most frequently used SMP by RLs, whereas Telegram was the most frequently used SMP by DLs. Facebook was the SMP least frequently used by both groups. There were also statistically significant differences in favor of RLs over DLs in the frequency of use of SMPs in preparation for exams due to the Covid-19 pandemic Most participants reported that SMPs have a positive effect on their academic achievements. During the pandemic this was the main reason for continuing to use SMPs. Other reasons that emerged from the qualitative analysis of the open-ended responses included educational, technical and cognition reinforcement. The study results suggested implications for learners, instructors and educational policy makers.